Presentasi Sinematik melalui Kontribusi Elemen Audio dalam Film Babi Buta yang Ingin Terbang - Hardiwan Prayoga (Jurnal Kajian Seni, 2017)
Film became concrete presentation of reality. Indonesian fi lm title Babi Buta yang Ingin Terbang was produced in 2006. Directed by Edwin, this fi lm focuses on the issue of Chinese families in Indonesia were giddy at her own identity when it comes to clash with the social environment. The fi lm uses the song I Just Call to Say I Love You, from Stevie Wonder were repeated in some parts of the fi lm, and sung in many different ways by almost all the characters. On the other hand, Film is basically elaborate audio and visual elements. Babi Buta yang Ingin Terbang has not attractive visual displays, the picture that appear with a static camera movement and shot in a long duration, this way extremely provoke boredom for the audience, in this position audio elements are present to contribute. Represent the viewpoint of the audience, this paper examines the technical side of cinematic presentations using audio elements as the medium, starting from how the fi lm uses the audio aspects of the cinematic presentation in its purpose narrating the premise.